Cultura associativa: a gênese do cooperativismo agropecuário de alimentos da mesorregião Oeste paranaense - Willers, Ednilse Maria (2015)
The main objective of this research was to analyze and understand the genesis of the food agricultural cooperativism in West mesoregion of Paraná State, through the associative culture of its founders. Therefore, we structured two fronts of research: a) the construction of a theoretical framework guided by the concept of associative culture and cooperative system and; b) the guided analysis framework in the training process, colonization and settlement of West mesoregion of Paraná State and the food agricultural cooperatives establishment related to that region. We identified the food agricultural cooperatives and selected them: Copacol (headquartered in the city of Cafelândia), C.Vale (headquartered in the city of Palotina), LAR (headquartered in the city of Medianeira), Coopavel (headquartered in Cascavel) and Copagril (headquartered in the city of Marechal Cândido Rondon). The methodology adopted was the qualitative approach, based on the descriptive-explanatory premise. The descriptive research allowed the analysis and description of the historical, economic and social context of Paraná State and of the West mesoregion, in the first decades of the twentieth century. This analysis allowed the junction and discussion of the elements that led to the creation, expansion and consolidation, over time, of the food cooperative system in the region under study. The explanatory research allowed us to understand the theoretical framework used. So, as the source of data we used secondary data, through bibliographical and documentary research. This methodological base led us to see that in the West mesoregion of Paraná State, the genesis of the five food agricultural cooperatives under investigation was due to the social needs of individuals, the settlers who have established them, since the 1960s. The foundation of these cooperative societies met the economic interests of the farmers, and not just of the government. In this study, the associative culture rescued through the memories of the settlers who established the cooperatives became the cultural touchstone maintained and reproduced by the community structure of the pioneer settlers. The dynamic of living together and community relations remained independent of macroeconomic changes in the country. This gregariousness, entrenched in the social structure of migrants, who settled the West mesoregion of Paraná, guided cooperation initiatives and triggered producer associations, and these ones, in the food agricultural cooperatives of the mesoregion under study.